Dissolution Kinetics of Smithsonite in Sulfamic Acid Solution - Wu1, Dan-Dan; Wen1, Shu-Ming; Yang2, Jing; Deng1, Jiu-Shuai; Jiang3, Li (Asian Journal of Chemistry, 2013)
This study investigated the dissolution kinetics of smithsonite by using sulfamic acid solution as an alternative leaching agent. Moreover, the effects of certain experimental parameters on the dissolution of smithsonite were investigated using a kinetic model. The dissolution rate was found to increase with increasing solution temperature, acid concentration and stirring speed, as well as with decreasing particle size. Moreover, the dissolution rate can be controlled by the shrinking core model for surface chemical reactions. The activation energy of the dissolution process was determined to be 42.86 kJ/mol. The results indicated that sulfamic acid solution could be used as a leaching agent for zinc extraction in smithsonite.